INTERSPECIFIC ASSOCIATION PATTERNS AND EDAPHlC FACTORS' INFLUENCES: A CASE STUDY OF Orania regalis Zippelius IN WAIGEO ISLAND, WEST PAPUA [Pola Asosiasi Antarspesies dan Pengaruh Faktor Edafik: Studi Kasus Orania regalis Zippelius di Pulau Waigeo, Papua Barat] - Didik Widyatmoko (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Tropical plant community ecology is often assumed to be driven largely by stochastic disturbance, regeneration and demographic processes. The influence and importance of physical and biotic components are rarely taken into account. Consequently, scientific findings in this field are very limited. Tropical soils are in fact more diverse than usually is recognized. This study was conducted to test hypotheses about the importance and influence of edaphic parameters and association patterns in determining the abundance and distribution of the Papuasian palm Orania regalis Zippelius and its co-occurrence with other plant species. The results showed that a number of interrelating edaphic factors, in combination, appeared to explain the abundance and occurrence of O. regalis. This palm showed a preference for wet, but well-drained soils, with high magnesium (Mg ) and calcium (Ca *)contents. The three largest colonies occurred in sites where Mg * content was high. On the other hand, high alkaline concentrations corresponded to the absence of the palm. Eight of 14 tropical plant species were positively associated while six species were negatively associated with O. regalis. For five species (Licuala gramnifolia, Tabernaemontana aurantiaca, Intsia bijuga, Vatica rassak,and Palaquium obovatum), the association with O. regalis was strong, as indicated by their Ochiai indices (>0.5).The palms L. gramnifolia and Sommieria leucophylla appeared to have similar ecological preferences and habitat requirements with O.regalis. The palm tended to occupy sites with lower C/N ratios and all known colonies occurred in habitats with average C/N values of less than 10. Based on the r-squared values, exchangeable Mg* appeared to have more influence on plant density and frequency than on basal area and canopy circle area. The exchangeable Ca * and C/N values showed a similar pattern to Mg contents.However, K ., Na ., Al and H contents did not show significant relationships with the palm abundance parameters. These findings suggest that edaphic variables and plant association patterns are important determinants of the abundance and occurrence of tropical plant species.